2004
DOI: 10.1038/sj.sc.3101581
|View full text |Cite
|
Sign up to set email alerts
|

Vocational reintegration following spinal cord injury: expectations, participation and interventions

Abstract: Study design: Survey. Objectives: To explore the process of reintegration in paid work following a traumatic spinal cord injury (SCI), including the role of early expectations of individual patients regarding return to work, indicators of success of job reintegration and a description of reintegration interventions and barriers. Setting: Dutch rehabilitation centre with special department for patients with spinal cord injuries. Methods: Descriptive analysis of data gathered by a mailed questionnaire, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 19 publications
(59 reference statements)
3
43
2
Order By: Relevance
“…[9][10][11][12][13] Factors related to the success of vocational reintegration are age, education level, realistic expectations, preinjury type of job, type of lesion and disease-specific problems and disabilities. 2,4,9,[14][15][16] For those people unable to reintegrate in work, participation in nonvocational activities must also be considered as a successful rehabilitation outcome. Very few studies have described the types of postinjury activities and roles other than traditional employment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] Factors related to the success of vocational reintegration are age, education level, realistic expectations, preinjury type of job, type of lesion and disease-specific problems and disabilities. 2,4,9,[14][15][16] For those people unable to reintegrate in work, participation in nonvocational activities must also be considered as a successful rehabilitation outcome. Very few studies have described the types of postinjury activities and roles other than traditional employment.…”
Section: Introductionmentioning
confidence: 99%
“…24 In our previous study on vocational reintegration, a reasonably good job satisfaction was found. 14 Information about the satisfaction with nonvocational activities is rare. 1,2 To improve rehabilitation interventions aimed at a satisfactory participation, it is important to know the perspectives of job reintegration, time use and satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…3,29 The promising outcomes for subjects with a habit of working indicates the importance of vocational rehabilitation, and clinicians must create and evaluate opportunities for patients to return to employment after discharge from rehabilitation. 45 Foreign subjects tended to have a lower level of different aspects of physical capacity. Not being Dutch negatively predicted strength and its recovery during the year after discharge.…”
Section: Prognostic Factorsmentioning
confidence: 93%
“…Further prospective data are needed to establish these proposed explanations. 45 Although there was no significant colinearity between sex and hours of employment, and although both predictors contributed to the explained variance simultaneously, it is difficult to rule out that the predictive effect of employment was mediated through a covariate such as sex. 3,29 The promising outcomes for subjects with a habit of working indicates the importance of vocational rehabilitation, and clinicians must create and evaluate opportunities for patients to return to employment after discharge from rehabilitation.…”
Section: Prognostic Factorsmentioning
confidence: 95%
“…The typical spectrum of activity limitations and participation restriction relate to mobility such as transfers and locomotion, [15][16][17][18] self-care activities such as bathing, dressing and toileting, 19,20 difficulties in regaining work, maintaining social relationships, participating in leisure activities and being active members of the community. 11,21 Given the activity limitations resulting from SCI, participation restrictions that a person with SCI might experience are highly dependent on environmental factors. 22 For many persons with SCI, barriers in the community are particularly related to mobility equipment and transportation.…”
Section: Introductionmentioning
confidence: 99%